Anti-nociceptive and Anti-inflammatory Effects of Withanone in Various Nociception and Inflammation-Induced Murine Model - Wang, Fengfeng; Zhu, Yunxia (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Pain is an unpleasant sensation that may result from severe or harmful stimuli. It serves as an indication that there may be a problem within the body and it can aid in ensuring the protection. Pain is a ubiquitous experience, with a significant prevalence worldwide. Pain can arise from various sources, including injury, disease, or even emotional trauma and its manifestation can range from acute to chronic. Objectives: The current work has focused at exploring the anti-inflammatory and antinociceptive properties in various mice model. Materials and Methods: The current study employed Swiss mice, inducing nociception by several chemical and thermal stimulation methods. The experimental mice were treated with withanone at various concentrations including 10, 20 and 30 mg/kg before to the induction of stimuli. The anti-inflammatory activity of withanone were assessed utilizing a carrageenan-initiated air pouch technique. The concentrations of inflammatory cytokines were evaluated using commercial kits. Results: The results of the current work demonstrated that the withanone has significantly improved the reaction time on hot plate, increased the response time during tail immersion in hot water, reduced writhing frequency and diminished licking reflexes in the mice. Furthermore, the withanone successfully diminished the carrageenan-induced upsurge in inflammatory markers in the experimental mice, indicating the anti-inflammatory potentials of withanone. Conclusion: The present findings emphasize the anti-nociceptive and anti-inflammatory activities of withanone in various chemical- and heat-induced inflammation and pain models.
Keywords: Carrageenan; Cytokines; Formalin; Nociception; Tail flick test; Withanone.